Long-Term, Fructose-Induced Metabolic Syndrome-Like Condition Is Associated with Higher Metabolism, Reduced Synaptic Plasticity and Cognitive Impairment in Octodon degus - Rivera, Daniela S.; Lindsay, Carolina B.; Codocedo, Juan F.; Carreno, Laura E.; Cabrera, Daniel; Arrese, Marco A.; Vio, Carlos P.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (My University, 2018)
There has been a progressive increase in the incidence of fructose-induced metabolic disorders, such as metabolic syndrome (MetS). Moreover, novel evidence reported negative effects of high-fructose diets in brain function. This study was designed to evaluate for the first time the effects of long-term fructose consumption (LT-FC) on the normal ageing process in a long-lived animal model rodent, Octodon degus or degu. Moreover, we could replicate human sugar consumption behaviour over time, leading us to understand then the possible mechanisms by which this MetS-like condition could affect cognitive abilities. Our results support that 28months (from pup to adulthood) of a 15% solution of fructose induced clinical conditions similar to MetS which includes an insulin-resistance scenario together with elevated basal metabolic rate and non-alcoholic fatty liver disease. Additionally, we extended our analysis to evaluate the impact of this MetS-like condition on the functional and cognitive brain processes. Behavioural test suggests that fructose-induced MetS-like condition impair hippocampal-dependent and independent memory performance. Moreover, we also reported several neuropathological events as impaired hippocampal redox balance, together with synaptic protein loss. These changes might be responsible for the alterations in synaptic plasticity and transmitter release observed in these cognitively impaired animals. Our results indicate that LT-FC induced several facets of MetS that eventually could trigger brain disorders, in particular, synaptic dysfunction and reduced cognition.
Keywords: octodon degus; fructose; insulin resistance; basal metabolic rate; non-alcoholic fatty liver; behaviour performance; synaptic plasticity